2021
DOI: 10.1016/j.heliyon.2021.e06637
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nutrition knowledge, attitude and practices of adolescent sports trainee: A cross-sectional study in Bangladesh

Abstract: Background Nutrition is an important predictor of an athlete's performance. It is more important for particularly those athletes who are in the growing stage (adolescents). This study aimed to assess their current level of knowledge, attitude, and practices (KAP) of nutrition and to predict potential factors impacting their level of these KAP. Methods A cross-sectional study was conducted among adolescent trainee athletes selected conveniently from 11 sports departments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Previous studies found significant differences in knowledge scores based on sex [ 5 , 8 , 26 ], BMI classification [ 26 ], and sports category [ 26 ], which we did not observe in this study. While the general principle of sports nutrition is universal for all athletes worldwide, different studies used different sets of questions and assessed different knowledge domains.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies found significant differences in knowledge scores based on sex [ 5 , 8 , 26 ], BMI classification [ 26 ], and sports category [ 26 ], which we did not observe in this study. While the general principle of sports nutrition is universal for all athletes worldwide, different studies used different sets of questions and assessed different knowledge domains.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, based on the correct response of the nutrition knowledge and practice score, the study participants demonstrated a relatively low level of nutrition knowledge and practice compared to previous findings where less than half had poor nutritional knowledge ( 16 , 43 , 44 ). The optimum nutrition knowledge is crucial for fostering athletic performance in athletes, which further shows that increasing nutrition knowledge is related to dietary intake and subsequent sports performance ( 10 , 45 ).…”
Section: Discussionmentioning
confidence: 55%
“…Different genetics of Iranians, Iranian traditional dishes and differences in their cooking methods and also higher physical activity level and nutritional knowledge among athletic v . non-athletic populations ( 29 31 ) are among key determinants that can affect body composition and distinguish athletic and non-athletic populations and these differences clarify the novelty of the present study. Thus, the aims of the present study were first to determine the HEI-2015 score of the diets consumed by athletes and second its association with different body composition parameters of soccer players and referees.…”
Section: Introductionmentioning
confidence: 80%